Identification of a transcriptional silencer in the 5'-flanking region of the human epsilon-globin gene. - Cao, S X (1989)
We have studied the 5'-flanking sequences required for the transcriptional regulation of human epsilon-globin gene expression. A series of deletion mutants of the human epsilon-globin gene 5'-flanking sequences were constructed and linked to the bacterial chloramphenicol acetyltransferase gene. Expression of these constructs was tested in HeLa cells and the human erythroleukemia K-562 cells. By measuring chloramphenicol acetyltransferase activities and mRNA levels we found that the sequence between -177 and -392 base pairs (bp) relative to the mRNA initiation site exerts a negative effect on epsilon-globin promoter activity. This effect is more pronounced in HeLa cells compared with K-562 cells. To further characterize the negative control region we cloned the DNA sequence between -177 and -392 bp either 5' or 3' of the epsilon-globin promoter and in either orientation. Our data indicate that this negative control region inhibits the epsilon-globin promoter activity in a position- and orientation-independent manner, thus suggesting that it is a silencer. In addition, the silencer also inhibits the expression from the Herpesvirus thymidine kinase promoter. Sequence comparison reveals that there are three short regions within the silencer that share extensive homology with those found in other negative control DNA elements. Our results therefore indicate that an upstream silencer element is present in the epsilon-globin gene and that it may play an important role in the control of epsilon-globin gene expression during development.